1, 3, 5‐Triphenylbenzene Based Porous Conjugated Polymers for Highly Efficient Photoreduction of Low‐Concentration CO2 in the Gas‐Phase System. Issue 4 (29th December 2021) - Dai, Chunhui; Zhong, Lixiang; Wu, Wei; Zeng, Chao; Deng, Yue; Li, Shuzhou
Abstract : Herein, three 1, 3, 5‐triphenylbenzene based porous conjugated polymers (PCPs) are designed for photochemical reduction of CO2 in simulated flue gas in the mild gas−solid reaction system. By tuning the nature of the comonomers, the PCPs present high surface areas, high CO2 /N2 selectivity, and broad visible light absorptions with bandgaps of 1.81−2.07 eV. At 1 bar and 273 K, the CO2 uptake capacity of PCPs is enhanced from 1.28 to 2.18 mmol g −1, with an increase in CO2 adsorption heat from 21.8 to 28.3 KJ mol −1 . In the presence of gaseous water, SO‐TPB demonstrates the highest CO production rate of 40.12 μmol h −1 g −1 and nearly 100% product selectivity without using organic sacrificial reagent and additional cocatalyst (>420 nm). Moreover, SO‐TPB can be recovered while well retaining the photocatalytic activity and reused at least five runs, indicating good recyclability. Abstract : Herein, for the first time, three 1, 3, 5‐triphenylbenzene based porous conjugated polymers for CO2 photoreduction in the simulated flue gas system are reported. Compared with fluorene, the incorporation of the heterocycle comonomer is demonstrated to efficiently improve the CO2 capture selectivity, photoinduced charge transport, and the final photocatalytic activity under visible light (>420 nm).